Effects of Adding an Internet-Based Pain Coping Skills Training Protocol to a Standardized Education and Exercise Program for People With Persistent Hip Pain (HOPE Trial): Randomized Controlled Trial Protocol. Issue 10 (1st October 2015) - Bennell, Kim L.; Rini, Christine; Keefe, Francis; French, Simon; Nelligan, Rachel; Kasza, Jessica; Forbes, Andrew; Dobson, Fiona; Haxby Abbott, J.; Dalwood, Andrew; Vicenzino, Bill; Harris, Anthony; et al.
Abstract : Background: Persistent hip pain in older people is usually due to hip osteoarthritis (OA), a major cause of pain, disability, and psychological dysfunction. Objective: The purpose of this study is to evaluate whether adding an Internet-based pain coping skills training (PCST) protocol to a standardized intervention of education followed by physical therapist–instructed home exercise leads to greater reductions in pain and improvements in function. Design: An assessor-, therapist-, and participant-blinded randomized controlled trial will be conducted. Setting: The study will be conducted in a community setting. Participants: The participants will be 142 people over 50 years of age with self-reported hip pain consistent with hip OA. Intervention: Participants will be randomly allocated to: (1) a control group receiving a 24-week standardized intervention comprising an 8-week Internet-based education package followed by 5 individual physical therapy exercise sessions plus home exercises (3 times weekly) or (2) a PCST group receiving an 8-week Internet-based PCST protocol in addition to the control intervention. Measurements: Outcomes will be measured at baseline and 8, 24, and 52 weeks, with the primary time point at 24 weeks. Primary outcomes are hip pain on walking and self-reported physical function. Secondary outcomes include health-related quality-of-life, participant-perceived treatment response, self-efficacy for pain management and function, pain coping attempts, pain catastrophizing, and physical activity. Measurements of adherence, adverse events, use of health services, and process measures will be collected at 24 and 52 weeks. Cost-effectiveness will be assessed at 52 weeks. Limitations: A self-reported diagnosis of persistent hip pain will be used. Conclusions: The findings will help determine whether adding an Internet-based PCST protocol to standardized education and physical therapist–instructed home exercise is more effective than education and exercise alone for persistent hip pain. This study has the potential to guide clinical practice toward innovative modes of psychosocial health care provision.